A Diagnosis of Insomnia Is Associated With Differential Expression of Sleep-Regulating Genes in Military Personnel. (July 2015) - Gill, Jessica M.; Lee, Hyunhwa; Baxter, Tristin; Reddy, Swarnalatha Y.; Barr, Taura; Kim, Hyung-suk; Wang, Dan; Mysliwiec, Vincent
Sleep disturbance is a common and disturbing symptom in military personnel, with many individuals progressing to the development of insomnia, which is characterized by increased arousals, wakefulness after sleep onset, and distorted sleep architecture. The molecular mechanisms underlying insomnia remain elusive, limiting future therapeutic development to address this critical issue. We examined whole gene expression profiles associated with insomnia. We compared subjects with insomnia ( n = 25) to controls ( n = 13) without insomnia using microarray gene expression profiles obtained from peripheral samples of whole blood obtained from military personnel. Compared to controls, participants with insomnia had differential expression of 44 transcripts from 43 identified genes. Among the identified genes, urotensin 2 was downregulated by more than 6 times in insomnia participants, and the fold-change remained significant after controlling for depression, posttraumatic stress disorder, and medication use. Urotensin 2 is involved in regulation of orexin A and B activity and rapid eye movement during sleep. These findings suggest that differential expression of these sleep-regulating genes contributes to symptoms of insomnia and, specifically, that switching between rapid eye movement and nonrapid eye movement sleep stages underlies insomnia symptoms. Future work to identify therapeutic agents that are able to regulate these pathways may provide novel treatments for insomnia.